1992
DOI: 10.1088/0029-5515/32/2/i07
|View full text |Cite
|
Sign up to set email alerts
|

Radial current in a tokamak caused by a biased electrode

Abstract: It is demonstrated that measurements of radial electric currents excited from biased electrodes in TUMAN 3 and other tokamaks provide a crucial test in validating different models for L-H transitions. The results are assessed from the viewpoint of a previously developed theory, which is briefly described. There is evidence from the voltage-current characteristics in TUMAN 3 which corroborates features of this theory. A spontaneously occurring Ohmic H-mode is switched off when a substantial positive biasing vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 8 publications
5
50
0
Order By: Relevance
“…This result is not a surprise: many tokamak experiments have documented that the damping of flows in the symmetry direction ͑the toroidal direction in that case͒ is faster than neoclassical theory predicts. 45,[47][48][49][50][51][52] In this sense, the damping of flows in the quasisymmetric HSX is similar to that in axisymmetric tokamaks.…”
Section: Discussion Of Enhanced Flow Damping In Hsxmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is not a surprise: many tokamak experiments have documented that the damping of flows in the symmetry direction ͑the toroidal direction in that case͒ is faster than neoclassical theory predicts. 45,[47][48][49][50][51][52] In this sense, the damping of flows in the quasisymmetric HSX is similar to that in axisymmetric tokamaks.…”
Section: Discussion Of Enhanced Flow Damping In Hsxmentioning
confidence: 99%
“…45 Rozhansky and Tendler 46 have constructed a model that approximately predicts the radial conductivity in the L mode in TUMAN-3. This model assumes that there exists anomalous shear viscosity to damp the toroidal flow.…”
Section: ٌ͉͉͗͘mentioning
confidence: 99%
“…On several tokamaks (CCT [204,205], TUMAN-3 [206], TEXTOR [207] and others) biasing experiments were performed, where a biased electrode was inserted into the core plasma. Thus the potential of the order of few hundred eV was applied to the core flux surface with respect to the limiter, and the current-voltage characteristic was measured.…”
Section: Simulation Of Biasing Experimentsmentioning
confidence: 99%
“…Biased electrode experiments in tokamaks, [5]- [7] have shown that there is a sudden jump in the radial electric field during the L-H transition about a poloidal Mach number where is the speed of light, is the radial electric field, is poloidal magnetic field, and is the thermal velocity of ions) of unity. These experiments indicated that the viscosity in tokamaks is nonlinear.…”
Section: Introductionmentioning
confidence: 99%